ANALISIS EFKTIVITAS KULIAH KERJA NYATA DARING DAN LURING STKIP MUHAMMADIYAH SAMPIT - Nur Kumala; Ifan Julianta; Siti Haliah (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2021)
In the 2020/2021 academic year, all universitas in Indonesia carry out Real Word Lectures (KKN) online and offline, this happenes because the world is being hit by the Covid-19 pandemic which limits one’s activities outside the home. During the Covid-19 pandemic, KKN participants were more required to educate the public about Covid-19 and motivate and offer offers to the problems faced by the community. The bad impect due to the Covid-19 pandemic is not only felt on the healty and economic side but also spreads to the education sector so that atudents are also required to provide aolutions to distance learning. The subjects in this study were 15 field supervisors, the Chairperson of the LPPM STKIP Muhammadiyah Sampit, and the chairoerson of the STKIP Muhammadiyah Sampit, with a purposive sampling techique. The research instrument used is a closed questionnaire. The analysis technique used is categorization using the average value and standard deviation. The results of the quantitative descriptive analysis show that the effectiveness of the implementation of online and offline real word lectures STKIP Muhammadiyah Sampit for the 2020/2021 academic year has an efeective category with a percentage of 70.59% and mean 111.941 with 17 subjects.